A Study of Para-educators in Dubai - Hassanieh, Yolla (2016)
The inclusion rights of children with special needs are governed by international laws and regulations. It is mandatory for children with special needs to be accompanied and aided by paraprofessionals whose rule is to support children with special needs during school. With a special focus on the United Arab Emirates, this research seeks to understand how para-educators are recruited to aid children with special needs at schools. While the government is focusing on improving the policies for special education and precisely inclusion, the hiring process remains vague and random. This dissertation seeks to put the topic into context as it brings in global experiences of how other countries recruit para-educators in special education, in order to suggest what could be replicated in the UAE. A brief definition of the selection criteria of para-educators can help avoid the serious implications of their random employment in special education. This research underwent a survey and in depth interviews with para-educators, special educators, and parents to gather data for an analysis of the current recruitment criteria for paras in special education in the UAE, in an attempt to reflect the reality of para-educators in the UAE and contribute slightly to an understanding of what could be a challenge to inclusion if recruitment of para-educators in special education is done randomly.